2017
DOI: 10.1016/j.jaci.2016.03.029
|View full text |Cite
|
Sign up to set email alerts
|

CD151, a laminin receptor showing increased expression in asthmatic patients, contributes to airway hyperresponsiveness through calcium signaling

Abstract: We identify a role for CD151 in human ASM contraction. We implicate CD151 as a determinant of AHR in vivo, likely through regulation of GPCR-induced calcium and PKC signaling. These observations have significant implications in understanding the mechanism for AHR and the efficacy of new and emerging therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…The protein was subsequently reassigned as Cluster of Differentiation 151 (CD151) (Ashman, 2002). Whilst early reports identified CD151 as a surface protein, CD151 is also expressed intracellularly (Hwang et al, 2019), including cytoplasmic vesicles, endothelial cell junctions and perinuclear regions (Liu et al, 2007;Qiao et al, 2017).…”
Section: Cd151mentioning
confidence: 99%
See 2 more Smart Citations
“…The protein was subsequently reassigned as Cluster of Differentiation 151 (CD151) (Ashman, 2002). Whilst early reports identified CD151 as a surface protein, CD151 is also expressed intracellularly (Hwang et al, 2019), including cytoplasmic vesicles, endothelial cell junctions and perinuclear regions (Liu et al, 2007;Qiao et al, 2017).…”
Section: Cd151mentioning
confidence: 99%
“…Immunohistochemical staining showed that CD151 was found to be strongly positive in the lungs, specifically in airway smooth muscle (Qiao et al, 2017), epithelial layers, endothelial cells and blood vessels (Sincock et al, 1997). Given its abundance in lung tissue, the role of CD151 in normal and pathological processes in airways is especially relevant.…”
Section: Cd151mentioning
confidence: 99%
See 1 more Smart Citation
“…This is largely because their short cytoplasmic tails are generally < 20 amino acids in length and lack canonical signaling motifs . However, several tetraspanins were recently shown to interact with intracellular signaling proteins such as phosphatidylinositol 3‐kinases (PI3K) and PKC . Tetraspanins can associate with a variety of transmembrane and cytosolic proteins to form tetraspanin‐enriched microdomains (TEMs), and influence cellular signaling pathways including cell proliferation, survival, adhesion, and motility .…”
mentioning
confidence: 99%
“…However, several tetraspanins were recently shown to interact with intracellular signaling proteins such as Abbreviations 2D, two-dimensional; CDK4, cyclin dependent kinase 4; Co-IP, Coimmunoprecipitation; DMSO, dimethyl sulphoxide; EGF, Epidermal growth factor; HCC, hepatocellular carcinoma; IP, immunoprecipitation; NATsDB, Natural Antisense Transcripts Database; p-Akt, phosphorylated Akt; PI3K, phosphatidylinositol 3-kinases; p-GSK3b, phosphorylated GSK3b; PKB, protein kinase B; qRT-PCR, quantitative real-time PCR; Rb, retinoblastoma; TEMs, tetraspanin-enriched microdomains; TSPAN31¸tetraspanin 31; 3 0 UTR 3 0 untranslated regions. phosphatidylinositol 3-kinases (PI3K) and PKC [9][10][11]. Tetraspanins can associate with a variety of transmembrane and cytosolic proteins to form tetraspaninenriched microdomains (TEMs), and influence cellular signaling pathways including cell proliferation, survival, adhesion, and motility [12,13].…”
mentioning
confidence: 99%